Peningkatan Pemahaman Desain Interior Ramah Lingkungan Bagi UMKM - Juli Atika; Rani Hermita; Elsa Aditya; Ajeng Resti Ajilah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in driving local and national economic growth. However, in the development of business spaces, environmentally friendly aspects of interior design often receive less attention. This research aims to increase MSME actors' understanding of the principles of sustainable and environmentally friendly interior design. The method used is an educational approach through training and workshops for a number of MSME players in the culinary and retail sectors. The material presented includes selecting environmentally friendly materials, managing natural lighting, cross ventilation, and energy efficient space planning. The evaluation results show an increase in participants' knowledge and awareness of the importance of implementing environmentally friendly interior design, which also has an impact on operational cost efficiency and improving business image. Thus, it is hoped that this program can encourage the creation of MSME business spaces that are not only functional and visually attractive, but also support environmental sustainability.